2019
DOI: 10.1002/jcp.28489
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA B4GALT1‐AS1 promotes colon cancer cell stemness and migration by recruiting YAP to the nucleus and enhancing YAP transcriptional activity

Abstract: Here, an RNA‐sequencing assay revealed long noncoding RNAs (lncRNAs) with an ectopic expression between colon cancer (CC) and normal colon epithelial cells, in which lncRNA B4GALT1‐AS1 exhibited the highest change. A 3‐(4,5‐dimethythiazol‐2‐yl)‐2,5‐diphenyl tetrazolium bromide assay indicated that B4GALT1‐AS1 knockdown had no effect on CC cell viability, however, cell clone formation analysis showed that B4GALT1‐AS1 knockdown attenuated the capacity of cell clone formation. Additionally, gene set enrichment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Recently, lncRNAs are emerging as a critical mediator in a wealth of carcinogenic processes by targeting various downstream executors in Hippo signalling pathways (Figure 2). A number of lncRNAs, including B4GALT1 antisense RNA 1 (B4GALT1‐AS1), 35 gastric cancer high expressed transcript 1 (GHET1) 36 and X‐inactive specific transcript (XIST), 37 were tightly associated with YAP to exert their functions in cancers. Zhang et al 35 found that lncRNA B4GALT1‐AS1 was highly expressed in colon cancer cells by RNA‐seq.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lncRNAs are emerging as a critical mediator in a wealth of carcinogenic processes by targeting various downstream executors in Hippo signalling pathways (Figure 2). A number of lncRNAs, including B4GALT1 antisense RNA 1 (B4GALT1‐AS1), 35 gastric cancer high expressed transcript 1 (GHET1) 36 and X‐inactive specific transcript (XIST), 37 were tightly associated with YAP to exert their functions in cancers. Zhang et al 35 found that lncRNA B4GALT1‐AS1 was highly expressed in colon cancer cells by RNA‐seq.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…A number of lncRNAs, including B4GALT1 antisense RNA 1 (B4GALT1‐AS1), 35 gastric cancer high expressed transcript 1 (GHET1) 36 and X‐inactive specific transcript (XIST), 37 were tightly associated with YAP to exert their functions in cancers. Zhang et al 35 found that lncRNA B4GALT1‐AS1 was highly expressed in colon cancer cells by RNA‐seq. Depletion of B4GALT1‐AS1 repressed cancer cell colony formation and stemness.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…Apart from being regulated by Hippo signaling, YAP is modulated by other pathways, such as, mechanical pressure [ 14 ] and Rho-GTPase [ 15 , 16 ]. Recent works showed that lncRNAs are associated with YAP activity, such as lncRNA B4GALT1-AS1 [ 17 , 18 ], lncRNA TUG1 [ 19 ], and lncRNA THOR [ 20 ], in which YAP transcriptional activity is responsible for lncRNA-mediated regulation on cell stemness; these effects supporting the promoting role of YAP in tumor cell stemness [ 21 , 22 ]. Moreover, it is indicated that MALAT1 induces YAP activity contributing to the stemness-related traits of esophageal squamous cell carcinoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the growth‐promoting effect of YAP has been shown to be critical for the proliferative response observed during intestinal inflammation as well as in sporadic CRC (Avruch, Zhou, & Bardeesy, ; Taniguchi et al, ). More interestingly, the stemness‐stimulating effect of a long noncoding RNA B4GALT1‐AS1 in human colon cancer cells has been attributed to its direct interaction with YAP, resulting in an enhancement of the transcriptional activity of YAP (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%